General techniques in Western blotting: towards effective and accurate immunoblot detection of proteins from cell lysate - Mohd Nasir, Mohd Hamzah; Kamaruzzaman, Puteri Amirah Adib; Othman, Mohd Saiful; Muhamad Azdhar, Muhamad Shahrizar (2019)
Western blotting also known as immunoblotting is a technique which was widely used in the detection of proteins. The protein of interest can be derived from various biological products. Western blotting receives its name due to the popular Southern blot (for DNA detection). The specificity of this technique is mainly dictated by the set of antibodies used for each western blotting experiment. The precise binding between an antibody and its target protein epitope allows detection of highly specific amino acid sequence within a protein. Thus, proper experimental design and material selection is a must prior to the experiment.